Analisis Elemen Dimensi Berkebhinekaan Global Dalam Ekstrakurikuler Karawitan - Wirani Nur Patria; Muhammad Abduh (Elementary Teacher Education Program, Majalengka University, 2023)
One dimension of the Pancasila student profile that must be instilled in students is global diversity. This dimension emphasizes character development through preserving cultural identity, appreciating diversity, and avoiding cultural isolation. The purpose of this study is to analyze the elements of the global diversity dimension through extracurricular karawitan at SD N 8 Wirosari. This research used case study-based qualitative methodology. The research subjects were the principal, karawitan extracurricular teacher and 18 students who participated in karawitan extracurricular activities. Data collection methods include documentation, observation, and interviews. Data analysis using the Miles and Huberman model method and data validation using triangulation which includes data reduction, data exposure, conclusion drawing, and verification. The research findings show that extracurricular karawitan encourages the development of four dimensional elements of global diversity, namely recognizing and respecting culture, intercultural communication and interaction, reflection and responsibility regarding the experience of diversity, and social justice. This research is expected that students can improve and implement the character of global diversity in everyday life.